3D reconstruction of bias effects on porosity, alignment and mesoscale structure in electrospun tubular polycaprolactone. (12th October 2021) - Liu, Y.; Chaparro, F.J.; Gray, Z.; Gaumer, J.; Cybyk, D.B.; Ross, L.; Gosser, J.; Tian, Z.; Jia, Y.; Dull, T.; Yarin, A.L.; Lannutti, J.J.
Abstract: Porosity variations in tubular scaffolds are critical to reproducible, sophisticated applications of electrospun fibers in biomedicine. Established laser micrometry techniques produced 14, 000 datapoints enabling thickness and porosity plots versus both the azimuthal (Φ) and axial (Z) directions following cylindrical mandrel deposition. These 3D datasets could then be 'unrolled' into 'maps' revealing variations in thickness and porosity versus 0, −5, and −15 kV collector biases. As bias increases, thinner, more 'focused' depositions occur. At 0 kV bias, maximum thickness coincides with maximum porosity; at −5 kV bias, maximum thickness coincides with minimum porosity. Porosity maps show that at 0 kV, a concave-down central region of higher ( 93–94%) porosity exists bounded on either side by roughly symmetric, parabolic decreases to 87–89% which corresponds to 15v%. At −5 kV, a different concave-up character occurs, showing a central porosity of 82–84% bounded by symmetric, parabolic increases in porosity to 85–86%. At −15 kV, the porosity profile shows either concave-up or linear behavior. Simultaneous decreases in net porosity versus bias (91.1%@0 kV > 83.4%@-5 kV > 80.2%@-15 kV) are sensible, but significant changes in the distribution were unexpected. Surprisingly, at 0 kV, extensive mesoscale surface roughness is evident. Optical profilometry revealed unique features 1600 × 420 μm in size, standing 210 μm above the surrounding surface. These shrink to only 440 × 150 μm in size and 30 μm higher at −5 kV bias and disappear entirely at −15 kV. Scanning electron microscopy (SEM) resolved these into novel, localized 'domains' containing tightly aligned fibers oriented parallel to the mandrel axis. Observation of 'curly' fibers in the SEMs following −5 and −15 kV indicate buckling instabilities. This agrees with prior observations of residual solvent effects: increased bias causes faster motion toward the mandrel, meaning (1) its solvent content upon arrival is higher, leading to lower viscosities less resistant to buckling/compaction, (2) higher velocities during deposition cause both decreased porosity/"denser packing" and increased buckling. Unexpectedly, we also observed substantial orientation along the mandrel axis. By modifying classical bending instability models to incorporate cylindrical electric fields, simulation revealed that horizontal components in the modified electric field alter bending loop shape, causing the observed alignment. This provides a new, easily utilized tool enabling facile, efficient tuning of orientation. Graphical abstract: Image 1 Highlights: Electrospun depositions at 0, -5 and -15 kV were characterized by laser metrology. 3D reconstructions reveal strong sensitivity of thickness and porosity to bias. Predominant axial fiber alignment was connected to the cylindrical electric field. Novel observations of exquisitely aligned fiber bundles within the deposit were made. Laser-based interrogation provides a powerful means of electrospun characterization.